Transforming growth factor-β activated kinase 1 (Tak1) is activated in hepatocellular carcinoma, mediates tumor progression, and predicts unfavorable outcome - Ridder, Dirk; Urbansky, Lana Louisa; Witzel, Hagen Roland; Schindeldecker, Mario; Weinmann, Arndt; Berndt, Kristina; Gerber, Tiemo Sven; Köhler, Bruno Christian; Nichetti, Federico; Ludt, Annekathrin; Gehrke, Nadine; Schattenberg, Jörn Markus; et al. (Cancers, 2022)
Although knowledge on inflammatory signaling pathways driving cancer initiation and progression has been increasing, molecular mechanisms in hepatocarcinogenesis are still far from being completely understood. Hepatocyte-specific deletion of the MAPKKK Tak1 in mice recapitulates important steps of hepatocellular carcinoma (HCC) development, including the occurrence of cell death, steatohepatitis, dysplastic nodules, and HCCs. However, overactivation of Tak1 in mice upon deletion of its deubiquitinase Cyld also results in steatohepatitis and HCC development. To investigate Tak1 and Cyld in human HCCs, we created a tissue microarray to analyze their expression by immunohistochemistry in a large and well-characterized cohort of 871 HCCs of 561 patients. In the human liver and HCC, Tak1 is predominantly present as its isoform Tak1A and predominantly localizes to cell nuclei. Tak1 is upregulated in diethylnitrosamine-induced mouse HCCs as well as in human HCCs independent of etiology and is further induced in distant metastases. A high nuclear Tak1 expression is associated with short survival and vascular invasion. When we overexpressed Tak1A in Huh7 cells, we observed increased tumor cell migration, whereas overexpression of full-length Tak1 had no significant effect. A combined score of low Cyld and high Tak1 expression was an independent prognostic marker in a multivariate Cox regression model.
Gesehen am 21.09.2022